Access to and utilisation of health care among people living with HIV/AIDS in Mankweng /Polokwane area - Modiba, Mantwa Welhemina (My University, 2009)
The aims of the study was to investigate if people living with HIV/AIDS (PLWHA) have access to health care, to determine utilisation patterns and to investigate how gender differences, socioeconomic, geographic location, and cultural beliefs influence access to and the utilisation of health care among PLWHA. Methods: This was a quantitative study based on a cross-sectional design. The study comprised of 200 participants (45% males and 55% females), of which 71% were unemployed. Twenty-eight (28%) survive by the disability grant due to the illness as well as child support grants. Sixty eight (68%) were diagnosed with HIV/AIDS for the duration of 3-5 years. Descriptives, frequencies and ANOVA were employed to analyse data. Results: Participants were found to have access to and to utilise health care services. There was no gender differences found with regard to access to and utilisation of health care, but there was however a significant (p<.05) difference in gender and educational level interaction. Educational level and geographical location were found not to influence the actual access and utilisation rather, it determined the type of health care service utilised. Participants with higher educational levels, and those who reside in urban areas were significantly (p<.05) found to utilise private health care services than primary health care. Cultural beliefs were found not to influence access to and utilise of health care services. Conclusion: Barriers outlined for non-use of primary health care services need immediate attention in order to maximise access to and utilisation of primary health care services by PLWHA.
Thesis (MA (Clinical Psychology)) --University of Limpopo, 2009
Keywords: Health care; HIV/AIDS; 362.1969792; AIDS (Disease) -- Patients -- South Africa; Clinical psychology